Benefícios ecossistêmicos e econômicos do Parque Nacional da Chapada dos Guimarães - Maira Luiza Spanholi; Francisco Eduardo Mendes; Lucas de Almeida Nogueira da Costa; Lucas Rolo Fares; Carlos Eduardo Frickmann Young (Confins)
National Parks are areas created to protect biodiversity and promote sustainable development. The objective of this work is to demonstrate the importance of the Chapada dos Guimarães National Park (CGNP) in preventing deforestation and providing economic and environmental benefits in the region in which it is located. For this, using different methodologies of environmental economic valuation, the reduction of greenhouse gas emissions and soil erosion by avoided deforestation was calculated, as well as the park's influence on the use of surface water, ecological ICMS and public use. It was estimated that the CGNP avoided around 10,000 hectares of deforestation, preventing the erosion of 195,000 tons of soil per year and the total emission of 1.5 million tCO2e. The CGNP influences up to 45.2% of water consumption in the Cuiabá River basin, with an estimated influence on water consumption of up to R$73.9 million. In 2019, R$ 937 thousand were transferred to Cuiabá and Chapada dos Guimarães as ecological ICMS due to the existence of the CGNP. It was also estimated that the visit to the PNCG induced R$ 60.1 million per year in the production of local goods and services through the multiplier effect of the expenses that were made by visitors in the year 2019. Therefore, protected areas, such as the CGNP, are capable of preventing deforestation and silting up of rivers, helping to mitigate climate change due to their capacity to store carbon dioxide, in addition to serving as inducers of economic development in the region in which they are located.